A Case of Neurosarcoidosis-Induced Syndrome of Inappropriate Secretion of Antidiuretic Hormone Diagnosed with Neuroendoscopy - Shiko Gen; Akio Ogawa; Koji Kanai; Kanako Nobe; Naofumi Ikeda; Atsuko Mochizuki; Kazuo Tokushige (Case Reports in Medicine)
We treated a patient with neurosarcoidosis, which caused the syndrome of inappropriate secretion of antidiuretic hormone (SIADH), in whom diagnosis was performed using neuroendoscopy. The patient was a 56-year-old female who was hospitalized for hyponatremia and diagnosed with SIADH based on a detailed examination. During the course, she developed impaired consciousness due to acute hydrocephalus, which improved after ventricular drainage. Head magnetic resonance imaging (MRI) confirmed nodular lesions at the floor of the third ventricle and the cerebral aqueduct. Neuroendoscopic biopsy led to the diagnosis of neurosarcoidosis. Her hyponatremia improved after steroid therapy. Neurosarcoidosis can cause SIADH, and complication of hydrocephalus may lead to a poor prognosis. Neuroendoscopy appears to be effective for the diagnosis of neurosarcoidosis with hydrocephalus and helps in deciding the treatment modality.